Análisis del gasto del Gobierno Regional de Loreto período 2018-2022 - Macedo Pinche, Wilfredo David (2024)
The public entity in charge of addressing the needs of the population and promoting its development in the Loreto region is the Regional Government. This thesis aims to analyze the spending made by the National Government in the Loreto region during the period 2018-2022. To carry out this analysis, a descriptive approach was used, quantitative in nature and with a non experimental design. The study covered the accrual phase execution of Current Expenses and Capital Expenses. The results reveal an annual increase in the expenses of the Regional Government of Loreto. It is highlighted that most of the expenditure focused on Current Expenses, reaching S/ 7,737.71 million, which is equivalent to 76.60% of the total. In contrast, Capital Expenses totaled S/ 2,363.70 million, representing 23.40% of the expense. Current Expenses were mainly concentrated in the "Personal and Social Obligations" category with an amount of S/ 5,054.04 million (65.32% of the total), followed by "Goods and Services" with S/ 1,953.54 million (25.25% of the total). On the other hand, Capital Expenses stood out in the category "Acquisitions of Non-Financial Assets" with an amount of S/ 2,315.32 million (97.95% of the total), followed by "Other Expenses" with S/ 30.02 million (1.27%), which includes the acquisition of real estate, capital assets and equipment necessary for permanent actions, as well as the replacement of equipment.